Integration of GIS, AHP and TOPSIS in evaluating suitable locations for industrial development: A case of Tehri Garhwal district, Uttarakhand, India. (20th November 2019) - Ramya, Sakkeri; Devadas, V.
Abstract: Stability in demography and economy of a region can be maintained by generating employment opportunities with due consideration of locally available resources would be the best initiative to ensure and maintain sustainable development. The aim of the present study is to identify suitable locations for agro-based industrial use in Tehri Garhwal district of Uttarakhand State, India. Geographical Information System - GIS serves as an effective tool for identifying and monitoring the changes occurring in a specific region, and its associated impact on ecosystems. Multi-criteria decision making (MCDM) techniques like Analytical Hierarchy Process (AHP) and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) provides structural and pairwise quantification, and comparison between elements, and criteria for priority ranking for industrial location purpose. Topographical features, soil characteristics, connectivity, settlements, natural resources and their constraints, availability of raw material, labour availability, location of barren lands, climate and vicinity of major functional centres are the parameters considered in this study. Expert's opinions were consulted in determining the weights to the parameters and subsequently, the industrial land suitability map was generated. It was estimated that 0.06% (2.54 sq. km) of the study area is highly suitable for establishing industries in general, 1.51% (59 sq. km) is moderately suitable, 2.34% (91.52 sq. km) is least suitable and 96.09% (3764 sq. km) is permanently unsuitable for locating industries. In conclusion, this study highlighted the most suitable alternative/parcel through priority ranking by using GIS – MCDM (AHP & TOPSIS) and is a cost-effective tool for decision making in land-use planning and management. Highlights: Sustainable development/use of land is one of the important factors for economic growth. Land suitability assessment serve as a policy and planning tool for locating Industrial economic zones. GIS based multi-criteria decision-making process was used for suitability analysis. Integrated GIS, AHP and TOPSIS in evaluating best suitable location for agro-based industrial development. We identified alternative areas (agro-based industrial zones) and verified the parcels using Google Earth Pro.